Determination of Boron Content in Surface Paintings From Historical Stained-Glass Windows - Maestro-Guijarro, Laura (2025)
Stained-glass windows are often painted with grisailles and enamels. These glassy materials have a low melting temperature and are fixed to the base glass by firing processes. Lead and/or boron are commonly added to the painting material to lower their melting temperature so that they can melt without deforming the glass support. In the present study, model glass samples (with well-known boron content), replica and historical materials were analysed for their composition using Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) and Laser Induced Breakdown Spectroscopy (LIBS). The imprint left on the analysed samples after laser irradiation was observed using optical profilometry. The feasibility of using LIBS in situ as a suitable quantitative analytical technique to detect the presence of boron in historical enamels even in very small quantities was assessed. Quantitative information on historical Spanish enamels and grisailles was obtained from calibration curves generated from the model glass samples with known boron content. The proposed procedure enables a satisfactory chemical quantitative study of historical glass materials in situ, regardless of their size, provenance, and chronology.